Stakeholder engagement in wildlife management: Does the public trust doctrine imply limits?. Issue 2 (February 2015) - Decker, Daniel J.; Forstchen, Ann B.; Pomeranz, Emily F.; Smith, Christian A.; Riley, Shawn J.; Jacobson, Cynthia A.; Organ, John F.; Batcheller, Gordon R.
ABSTRACT: Recent evolution of the wildlife management institution in the United States includes adoption of good governance principles, wherein stakeholders expect and are provided opportunities for input and involvement in making decisions about public wildlife resources. Concurrently and perhaps paradoxically, state wildlife agencies are encouraged to operate with fidelity to the public trust doctrine and the principles of public trust administration, which may require trust administrators (i.e., appointed commissioners and public wildlife managers) to keep trust beneficiaries (i.e., theoretically all citizens, but especially special interests) at arm's length (i.e., restricted from having undue control) with respect to directly influencing decision‐making. In addition, public trust administration includes citizens taking responsibility for holding trust administrators accountable and requires government to provide citizens recourse for doing so. In practice, however, accountability typically is achieved through political influence or litigation, both routes antithetical to efficient public trust resource administration. This set of potentially conflicting expectations—practicing good governance through citizens' engagement in wildlife decision‐making processes, limiting beneficiaries' direct influence on decisions of trust administrators, and citizens' responsibility for holding trust administrators accountable—creates an apparent conundrum for state wildlife agencies. As a catalyst for deliberation about the implications of public trust doctrine in the wildlife profession, we describe potential problems and suggest ways for public wildlife managers to perform their responsibilities with due diligence to the combined expectations and requirements of good governance and the public trust doctrine. © 2014 The Wildlife Society.